Acceleration of ASL‐based time‐resolved MR angiography by acquisition of control and labeled images in the same shot (ACTRESS). Issue 1 (20th March 2017) - Suzuki, Yuriko; Fujima, Noriyuki; Ogino, Tetsuo; Meakin, James Alastair; Suwa, Akira; Sugimori, Hiroyuki; Van Cauteren, Marc; van Osch, Matthias J. P.
Abstract : Purpose: Noncontrast 4D‐MR‐angiography (MRA) using arterial spin labeling (ASL) is beneficial because high spatial and temporal resolution can be achieved. However, ASL requires acquisition of labeled and control images for each phase. The purpose of this study is to present a new accelerated 4D‐MRA approach that requires only a single control acquisition, achieving similar image quality in approximately half the scan time. Methods: In a multi‐phase Look‐Locker sequence, the first phase was used as the control image and the labeling pulse was applied before the second phase. By acquiring the control and labeled images within a single Look‐Locker cycle, 4D‐MRA was generated in nearly half the scan time of conventional ASL. However, this approach potentially could be more sensitive to off‐resonance and magnetization transfer (MT) effects. To counter this, careful optimizations of the labeling pulse were performed by Bloch simulations. In in‐vivo studies arterial visualization was compared between the new and conventional ASL approaches. Results: Optimization of the labeling pulse successfully minimized off‐resonance effects. Qualitative assessment showed that residual MT effects did not degrade visualization of the peripheral arteries. Conclusion: This study demonstrated that the proposed approach achieved similar image quality as conventional ASL‐MRA approaches in just over half the scan time. Magn Reson Med 79:224–233, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.